2016
DOI: 10.1007/s12029-016-9886-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Distribution Width as a Predictor of Metastasis in Gastric Cancer Patients

Abstract: Our results showed that in patients with GC, PDW, one of the standard parameters measured in a complete blood count, is a predictor of metastasis. Therefore, the PDW may be an important consideration in the surgical and chemotherapeutic treatment planning of patients with GC. Treatment strategies should also take into account lymphocyte and platelet levels, both of which were shown to be significantly related to survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Increased PDW was found in gastric cancer and lung cancer [21,22], and has been demonstrated to have a poor prognostic impact in melanoma, thyroid cancer, colorectal cancer, and laryngeal cancer. Also, studies, found that an increased PDW was associated with advanced TNM stages and shortened OS in patients with nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PDW was found in gastric cancer and lung cancer [21,22], and has been demonstrated to have a poor prognostic impact in melanoma, thyroid cancer, colorectal cancer, and laryngeal cancer. Also, studies, found that an increased PDW was associated with advanced TNM stages and shortened OS in patients with nasopharyngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] In the case of gastrointestinal malignancies like gastric cancer, increase PDW was found to be associated with metastasis. [ 25 ] Inconsistency in PDW association with the cancers may partly be attributed to type of cancer and partly to ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…54 In normal individuals, there was a linear correlation between PDW and MPV, while in patients with cancer, there was no parallel relationship between them. 55 Previous studies showed that PDW is associated with poor prognosis in NSCLC, 56 gastric cancer, 57,58 and melanoma. 59 The statement on PDW is controversial in different cancer research, and the significance between PDW and malignancy has not been deeply explored.…”
Section: Discussionmentioning
confidence: 99%